Evaluation of In Vitro and In Vivo Antiviral Activities of Vitamin D for SARS-CoV-2 and Variants - Chee-Keng Mok; Yan Ling Ng; Bintou Ahmadou Ahidjo; Zhen Qin Aw; Huixin Chen; Yi Hao Wong; Regina Ching Hua Lee; Marcus Wing Choy Loe; Jing Liu; Kai Sen Tan; Parveen Kaur; De Yun Wang; et al. (MDPI AG, 2023)
The COVID-19 pandemic has brought about unprecedented medical and healthcare challenges worldwide. With the continual emergence and spread of new COVID-19 variants, four drug compound libraries were interrogated for their antiviral activities against SARS-CoV-2. Here, we show that the drug screen has resulted in 121 promising anti-SARS-CoV-2 compounds, of which seven were further shortlisted for hit validation: citicoline, pravastatin sodium, tenofovir alafenamide, imatinib mesylate, calcitriol, dexlansoprazole, and prochlorperazine dimaleate. In particular, the active form of vitamin D, calcitriol, exhibits strong potency against SARS-CoV-2 on cell-based assays and is shown to work by modulating the vitamin D receptor pathway to increase antimicrobial peptide cathelicidin expression. However, the weight, survival rate, physiological conditions, histological scoring, and virus titre between SARS-CoV-2 infected K18-hACE2 mice pre-treated or post-treated with calcitriol were negligible, indicating that the differential effects of calcitriol may be due to differences in vitamin D metabolism in mice and warrants future investigation using other animal models.